Disfungsi Peran Orang Tua Terhadap Pendidikan dan Masa Depan Anak di Timika (Kajian Pendidikan Agama Kristen di Desa Mapurjaya): Penelitian - Felani Soplanit; Selderika Patty; Meike Albertina Nenete; Sephliano Sahureka (PT PUSTAKA CENDEKIA GROUP, 2026)
This study aims to analyze parental role dysfunction in children's education and future from the perspective of Christian Religious Education in Mapurjaya Village, Mimika Regency. A descriptive qualitative approach was employed using observation, in-depth interviews, and documentation. Participants were purposively selected and included parents, children, religious leaders, teachers, and community leaders. Data were analyzed using the Miles and Huberman model combined with Spradley's ethnographic analysis. The findings indicate that parental role dysfunction is primarily influenced by external factors, including work demands, limited time, economic constraints, and insufficient ability to assist children with learning. Nevertheless, parents continue to support their children's education through motivation, attention, educational support, and character and faith development. The study concludes that the family is the primary educational institution in Christian Religious Education, and optimizing parental roles requires sustained collaboration among families, churches, and schools to strengthen children's education, Christian character formation, and future development.